2014
DOI: 10.1083/jcb.201308115
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde neurotrophin signaling through Tollo regulates synaptic growth in Drosophila

Abstract: The Toll-like receptor Tollo positively regulates growth of the Drosophila larval neuromuscular junction through the JNK pathway after activation by the neurotrophin Spätzle3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 80 publications
(152 reference statements)
2
58
0
Order By: Relevance
“…The Spz-3 signal seems to be received by the Toll-8 receptor at least in the pigmented area in the Ze and p S mutant strains. The same ligand/receptor relationship has been reported in the neuromuscular junction of D. melanogaster (27). Because our recent study has shown that the p S phenotype is controlled by the apt-like-encoding transcription factor (7), this Spz-3/Toll-8 signaling pathway likely interacts with the genetic circuit of apt-like and contributes to the phenotypic diversity of caterpillars.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The Spz-3 signal seems to be received by the Toll-8 receptor at least in the pigmented area in the Ze and p S mutant strains. The same ligand/receptor relationship has been reported in the neuromuscular junction of D. melanogaster (27). Because our recent study has shown that the p S phenotype is controlled by the apt-like-encoding transcription factor (7), this Spz-3/Toll-8 signaling pathway likely interacts with the genetic circuit of apt-like and contributes to the phenotypic diversity of caterpillars.…”
Section: Discussionmentioning
confidence: 79%
“…An important question is whether the Bmspz-3 gene works on melanization through the Toll signaling pathway. Because Spz-3 works as a ligand of Toll-8 in neuromuscle joint formation in D. melanogaster (27), siRNA of BmToll-8 was injected into Ze and p S larva, which resulted in the loss of pigmentation patterns in both strains (red arrowheads in Fig. 4 C and D, respectively), similar to the phenotypic change observed in the Bmspz-3-knockdown larva (Figs.…”
Section: Spz-3 Work As a Putative Ligand Of Toll-8 Inmentioning
confidence: 82%
“…Drosophila Toll receptors are highly expressed during embryogenesis, pointing to developmental functions (49,54). Indeed, a subset of Toll receptors, including Toll-7, function as neurotrophin receptors and are activated by members of the Spaetzle family in the developing nervous system (36,55). Drosophila Toll receptors were also recently shown to function as adhesion molecules during elongation of the antero-posterior axis of the embryo (56).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that trafficking of receptors in addition to Wit are altered in the mutants described above, and it is the altered signaling of these additional receptors that is at least partly responsible for the transmitter release phenotype. Drosophila motor nerve terminals express a cholecystokinin-like receptor (CCKLR), a toll-like receptor, a metabotropic glutamate receptor (mGluRA) and likely the insulin receptor (Ballard et al, 2014;Bogdanik et al, 2004;Chen and Ganetzky, 2012;Howlett et al, 2008). Loss of mGluRA increases evoked transmitter release (Bogdanik et al, 2004;Howlett et al, 2008), raising the possibility that increased mGluRA signaling might decrease transmitter release, which could explain the decreased transmitter release observed in these receptor trafficking mutants.…”
Section: Rtnl1 Affects Evoked Neurotransmitter Release From Multiple mentioning
confidence: 99%